Gender gap in physical activity and sport participation across the lifespan in Australia between 2016 and 2023 - Katherine B. Owen; Philip J. Clare; Rochelle Eime; Ding Ding; Binh Nguyen; Mengyun Luo; Tracy Nau; Lindsey J. Reece; Adrian Bauman (BMC Public Health)
Abstract Background The primary aim of this study was to examine the gender gap in specific types of leisure-time physical activity (including sport and active recreation) in Australians across the lifespan from 2016 to 2023. The secondary aim of this study was to examine trends in participation in specific types of leisure-time physical activity from 2016 to 2023. Methods This repeated cross-sectional study included sport and active recreation data from Ausplay (2016–2023) from a representative sample of participants aged five years and above in Australia. Gender inequalities in all leisure-time physical activity, active recreation, sport (team and individual), and walking were examined using prevalence ratios (relative inequalities) and mean differences (absolute differences). Results Among the 168,678 participants, the prevalence of all leisure-time physical activity, team sport, and walking remained consistent, while active recreation and individual sport participation increased between 2016 and 2023. The gender gap in each activity remained consistent across the eight years, with boys and men participating in higher levels of sport, especially team sport, while girls and women participating in higher levels of active recreation and walking. Conclusions Women and girls participate in lower levels of sport than men and boys across the eight years, possibly contributing to the gender gap in overall leisure-time physical activity levels. To address these disparities, there needs to be a comprehensive approach that creates inclusive, flexible, and enjoyable sporting environments, while also further promoting active recreation to cater to diverse needs encouraging long-term participation.